2010
DOI: 10.1111/j.1349-7006.2010.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ZNF143 in tumor growth through transcriptional regulation of DNA replication and cell‐cycle‐associated genes

Abstract: The cell cycle is strictly regulated by numerous mechanisms to ensure cell division. The transcriptional regulation of cell-cyclerelated genes is poorly understood, with the exception of the E2F family that governs the cell cycle. Here, we show that a transcription factor, zinc finger protein 143 (ZNF143), positively regulates many cell-cycle-associated genes and is highly expressed in multiple solid tumors. RNA-interference (RNAi)-mediated knockdown of ZNF143 showed that expression of 152 genes was downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
77
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 35 publications
8
77
0
1
Order By: Relevance
“…The cell cycle is strictly regulated by various mechanisms to ensure cell division and, thus, the transcriptional regulation of cell-cycle-related genes expression requires the orchestrated recruitment of transcription factors, but it remains to be elucidated. We and others have previously revealed that a transcription factor, zinc finger protein 143 (ZNF143), which is a human homologue of the Xenopus transcriptional activator, Staf, positively regulates many DNA replication and cell-cycle-associated genes (Myslinski et al , 2007; Izumi et al , 2010; Hernández-Negrete et al , 2011). In fact, according to the DNA microarray analysis with ZNF143 -specific small interfering RNA (siRNA) transfection, 41 (27.0%) genes were categorised as concerned with the cell-cycle/DNA replication, such as Aurora kinase B or High-mobility group box 2 , among the <0.4-fold downregulated 152 genes (Izumi et al , 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The cell cycle is strictly regulated by various mechanisms to ensure cell division and, thus, the transcriptional regulation of cell-cycle-related genes expression requires the orchestrated recruitment of transcription factors, but it remains to be elucidated. We and others have previously revealed that a transcription factor, zinc finger protein 143 (ZNF143), which is a human homologue of the Xenopus transcriptional activator, Staf, positively regulates many DNA replication and cell-cycle-associated genes (Myslinski et al , 2007; Izumi et al , 2010; Hernández-Negrete et al , 2011). In fact, according to the DNA microarray analysis with ZNF143 -specific small interfering RNA (siRNA) transfection, 41 (27.0%) genes were categorised as concerned with the cell-cycle/DNA replication, such as Aurora kinase B or High-mobility group box 2 , among the <0.4-fold downregulated 152 genes (Izumi et al , 2010).…”
mentioning
confidence: 99%
“…We and others have previously revealed that a transcription factor, zinc finger protein 143 (ZNF143), which is a human homologue of the Xenopus transcriptional activator, Staf, positively regulates many DNA replication and cell-cycle-associated genes (Myslinski et al , 2007; Izumi et al , 2010; Hernández-Negrete et al , 2011). In fact, according to the DNA microarray analysis with ZNF143 -specific small interfering RNA (siRNA) transfection, 41 (27.0%) genes were categorised as concerned with the cell-cycle/DNA replication, such as Aurora kinase B or High-mobility group box 2 , among the <0.4-fold downregulated 152 genes (Izumi et al , 2010). For example, ZNF143 plays a central role in regulating the mitochondrial transcriptional initiation and replication of mitochondrial DNA (Gérard et al , 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain the pcDNA3-hemagglutinin (HA)-HMGB1 or pcDNA3-HA-HMGB2, full-length HMGB1 or HMGB2 complementary DNA (cDNA) was prepared from each GST expression plasmid [26], and the NH 2 -terminal HA-tagged HMGB1 or HMGB2 cDNA was ligated into a pcDNA3 vector (Invitrogen, San Diego, CA, USA) [27,28]. Transient transfection and immunoprecipitation (IP) assays were performed as previously described [27].…”
Section: Plasmid Construction Transient Transfection and Immunoprecmentioning
confidence: 99%